HUBUNGAN PROFIL LIPID DAN KEJADIAN STROKE ISKEMIK DAN HEMORAGIK DI RUMAH SAKIT OTAK M. HATTA: ASSOCIATION BETWEEN LIPID PROFILE AND INCIDENCE OF ISCHEMIC AND HEMORRHAGIC STROKE AT AT M. HATTA BRAIN HOSPITAL - Putra, Harits Ariqoh; Yusria, Anna; Aktalina, Lucia; Lubis, Tifanni Tantina (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2025)
Stroke is a clinical syndrome characterized by focal or global cerebral dysfunction lasting 24 hours or more. Stroke has many risk factors, one of which is dyslipidemia. Dyslipidemia is a condition in which there is an increase in total cholesterol levels, an increase in triglycerides, or a decrease in high-density lipoprotein. This study will analyze the relationship between lipid profiles and the incidence of ischemic and hemorrhagic stroke using an analytical observational study method with a cross-sectional approach with a simple random sampling technique. The sample size was 109 medical record data that met the inclusion and exclusion criteria. The data collection technique used secondary data, then analyzed univariate and bivariate using the Chi-Square test. Based on the Chi-Square test, the p-value of total cholesterol levels = 0.005 (OR 3.370), and the p-value of Low-Density Lipoprotein (LDL) levels = 0.001 (OR 4.475) on the incidence of ischemic stroke compared to hemorrhagic stroke. Based on the results of this study, it is concluded that there is a relationship between total cholesterol and LDL with the incidence of ischemic stroke and hemorrhagic stroke. The higher the total cholesterol and LDL levels, the higher the risk of ischemic stroke and hemorrhagic stroke. AbstrakStroke merupakan sindroma klinis yang ditandai dengan adanya disfungsi cerebral fokal atau global dan berlangsung dalam 24 jam atau lebih. Stroke memiliki banyak faktor risiko, salah satunya adalah dislipidemia. Dislipidemia adalah kondisi di mana terjadinya peningkatan kadar kolesterol total, peningkatan trigliserida, atau penurunan high-density lipoprotein. Penelitian ini akan menganalisis hubungan profil lipid dengan kejadian stroke iskemik dan hemoragik dengan metode studi observasional analitik pendekatan cross sectional dengan teknik pengambilan sampel simple random sampling. Besar sampel sebanyak 109 data rekam medik yang memenuhi kriteria inklusi dan ekslusi. Teknik pengambilan data menggunakan data sekunder, kemudian dianalisis secara univariat dan bivariat menggunakan uji Chi-Square. Berdasarkan uji Chi-Square didapatkan nilai-p kadar kolesterol total = 0,005 (OR 3,370), dan nilai-p kadar Low-Density Lipoprotein (LDL) = 0,001 (OR 4,475) terhadap insidensi kejadian stroke iskemik dibandingkan stroke hemoragik. Berdasarkan hasil penilitian ini disimpulkan bahwa terdapat hubungan antara kolesterol total dan LDL dengan kejadian stroke iskemik dan stroke hemoragik. Semakin tinggi kadar kolestrol total dan LDL maka akan semakin meningkatkan risiko terjadinya stroke iskemik dan stroke hemoragik.